The Fight Against Corruption in Romania: Struggles to Adhere to the Rule of Law and the (De) Legitimization of the ACA. - Meqdadi, Leen (MacEwan University Student eJournal, 2023)
Romania’s desire to establish an efficient anti-corruption agency (ACA) dates back to its zeal for European Union (EU) membership. The former Prime Minister of Romania, Adrian Năstase (Social Democratic Party), played an important role in establishing the anti-corruption agency (ACA), specifically in the context of the country’s EU accession. In a comprehensive sense, Romania’s legislative and administrative framework for fighting corruption is well established. In this thesis, we will look at the actors involved in delegitimizing the ACA’s success, primarily the political opposition and the media, as well as the actors who have helped legitimize the ACA’s efficacy. Furthermore, the political divisiveness between the political opposition and the ACA has caused multi-level conflict within the Romanian government and will provide us with answers to a variety of questions concerning the delegitimization and legitimization of the ACA. Has the political opposition played a role in the negative impacts of the ACA by tarnishing the National Anticorruption Directorate’s (DNA) credibility? Does the political opposition foment limiting the role of effectiveness in the ACA by raising doubts about the agency’s political motivations?